y-13=-1

Simple and best practice solution for y-13=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-13=-1 equation:


Simplifying
y + -13 = -1

Reorder the terms:
-13 + y = -1

Solving
-13 + y = -1

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '13' to each side of the equation.
-13 + 13 + y = -1 + 13

Combine like terms: -13 + 13 = 0
0 + y = -1 + 13
y = -1 + 13

Combine like terms: -1 + 13 = 12
y = 12

Simplifying
y = 12

See similar equations:

| g(x)=2.2*x | | 6(X+3)=4(x-10) | | 4-y=-11 | | g(x)=2.2x | | -1+3.3333333333333333333333333333333h=-16 | | 2x+2(4x)-40=180 | | 27-2x=5x+6 | | y+13=26 | | 6m+36=-4m-4(5+m) | | 11+y=15 | | -.6u-9=-5 | | 2r+6=3r+3 | | 14-y=3 | | 0.28571428571428571428571428571429y+8=11 | | 5c+8-c=-8 | | 3x+1=x^2-5x+1 | | X(x+12)+27=0 | | 4a=8+6a | | X(z+12)+27=0 | | 1.2x-0.4=0.3(x+1) | | 0.625q+60=0 | | 5y+7=2y+16 | | 8-1.3333333333t=-12 | | -x+4x+7=-2x+5 | | 7n=n+6(8n-7) | | 4t-1=3t+7 | | x^2-16=2x^2-14x+21 | | 4x+5=10x-23 | | -.75n+7=25 | | 3-.2x=.3x-7 | | 5x-6=1-2x | | (a+3b)x+(a+3b)y= |

Equations solver categories